Gertrude Stein’s “Historic Drama” (1930) - Emeline Jouve (Sillages Critiques)
This paper is an analysis of Gertrude Stein’s staging of the dialectic between the past and the present in her 1930 “Historic drama” trilogy published in Last Operas and Plays. A writer of the “continuous present,” Gertrude Stein presentifies the past which she renews by playing with the old traditions to invent new dramatic forms. The playwright’s style is emblematic of her quest to revive a lost past in the “now” of the action from which absent/present voices emerge. This paradoxical incarnation of “pure voices” in Gertrude Stein’s “memory plays” opens the way to an ontological reflection on the meaning of “being” in the present.